Seasonal Abundance of Adult Fly Species on the Exposed Carcasses in Baghdad City - Abdul – Rassoul, M . S .; Augul, R. S .; Al – Saffar, H. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Adult of dipterous flies were collected monthly from exposed animals carcasses during the period from February 2006 to January 2007 in Baghdad city. The results obtained showed that flies could be collected all over the year with variation of their population density in different seasons. The majority of the collected species were abundant during Spring and late Autumn (at lowest numbers) . In this investigation, nineteen species confined to four families were collected; these families are: Calliphoridae, Muscidae, Sarcophagidae and Fanniidae. The species Musca domestica Linn .was the most abundant followed by Chrysomya megacephala ( Fabricius )  , while Pollenia sp . and Fannia sp . were the least abundant species.